Understanding Management Concepts through Development of their Tool Box: The case of total quality management - Ćwiklicki, Marek (Naše gospodarstvo/Our economy, 2016)
This paper offers an alternative approach to defining the management concept. The proposed methodology relies on the identification of tools supporting the given concept. The author assumed that the identification of tools’ evolution gives clearer insights into circumstances of constant development of—by its nature—a more general concept. The tools’ classification resembles a phylogenic tree and is based on the idea of an affinity diagram. To provide the proof for such reasoning, the total quality management (TQM) concept was chosen. This proposition can be useful for better understanding origins and the development of management thought. It clarifies relationships among methods constituting frameworks of quality management.